model integrasi kearifan lokal (ikarme) dalam melatihkan keterampilan komunikasi ilmiah mahasiswa - Siagian, Asister Fernando; Purba, Jon Roi Tua; Saragih, Richsya Octrasima (PendIPA Journal of Science Education, 2024)
This research aims to validate the IKARME learning model in training students' scientific communication skills. This research uses development research through a validation study design by testing two criteria, namely content validity and construct validity. Validation involved three experts through Focus Group Discussion (FGD) activities. The research results show that the IKARME model is valid and reliable. This is based on calculations using the Aiken formula, that the V value for each instrument item is 0.75 ≤ V ≤ 1 with a very valid category and the reliability coefficient for each aspect of validity is in the range of 100% so that the validity results developed are reliable. It was concluded that the IKARME model was declared valid both in terms of content validity and construct validity to be able to improve students' scientific communication skills.